2012
DOI: 10.3758/s13421-012-0267-4
|View full text |Cite
|
Sign up to set email alerts
|

When do learners shift from habitual to agenda-based processes when selecting items for study?

Abstract: Learners presumably attempt to allocate their study time to maximize reward, yet in some contexts, their study choices are driven by reading biases that would not maximize reward. For instance, when presented with items in a horizontal array that are worth different values if correctly recalled, learners will often first select the leftmost item (i.e., a reading bias), even when it is associated with the lowest value. In four experiments, we investigated the degrees to which various factors cause learners to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 37 publications
2
49
2
1
Order By: Relevance
“…The fact that time constraints did have an impact in Ariel and Dunlosky (2013) but not in the current study, however, highlights the fact that selectivity and value-directed remembering may not always be as impervious to time constraints as in the current study—in some cases, selectivity may indeed change as a function of timing—and there are a number of factors that warrant additional consideration. For one, participants in the present study were not required to determine the value of the information they were attempting to remember—values were explicitly noted during the study session.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The fact that time constraints did have an impact in Ariel and Dunlosky (2013) but not in the current study, however, highlights the fact that selectivity and value-directed remembering may not always be as impervious to time constraints as in the current study—in some cases, selectivity may indeed change as a function of timing—and there are a number of factors that warrant additional consideration. For one, participants in the present study were not required to determine the value of the information they were attempting to remember—values were explicitly noted during the study session.…”
Section: Discussioncontrasting
confidence: 57%
“…That evidence of value-directed remembering persisted despite time limitations might initially seem to conflict with recent work by Ariel and Dunlosky (2013), which demonstrated that participants were less value-driven in their item selections when under time pressure. Critically, however, participants in that study made item selections from triplet pairings that were presented to participants in a single row so as to activate habitual reading biases.…”
Section: Discussionmentioning
confidence: 57%
“…Although selecting items on the basis of reading habits can be effective in many situations (Ariel & Dunlosky, ), people's study decisions are greatly biased by habitual responding that would not maximize reward and result in poor agenda execution (Ariel & Dunlosky, ; Dunlosky & Ariel, ). Therefore, in another study, Ariel and Dunlosky () explored under what conditions learners shifted from habitual to agenda‐based processes when selecting items for study, and discovered two conditions: (1) not limiting selection time and (2) restricting the number of selections on each trial.…”
Section: Introductionmentioning
confidence: 99%
“…Although selecting items on the basis of reading habits can be effective in many situations (Ariel & Dunlosky, ), people's study decisions are greatly biased by habitual responding that would not maximize reward and result in poor agenda execution (Ariel & Dunlosky, ; Dunlosky & Ariel, ). Therefore, in another study, Ariel and Dunlosky () explored under what conditions learners shifted from habitual to agenda‐based processes when selecting items for study, and discovered two conditions: (1) not limiting selection time and (2) restricting the number of selections on each trial. For the former condition, in the researchers’ view, time pressure during item selection will discourage ABR (i.e., to choose high‐reward item for study first) and encourage learners to use quicker, less resource‐demanding processes (i.e., to choose leftmost item for study first); when ample time for item selection is available to construct an agenda, the participants should be more likely to use agenda‐based processes to make their study decisions (Ariel & Dunlosky, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation